Climate resilience in Rwanda: evaluating refugees’ and host populations’ vulnerability to risk - Dampha, NK; Salemi, C; Rappeport, W; Polasky, S; Gebreegziabher, A (Refugee Studies Centre, University of Oxford, 2022)
In Rwanda, refugees in camps and host populations often face high risks of climate-related hazards. Recent research assesses the potential of climate risk reduction strategies to reduce injury and loss of life, improve public health and well-being, and protect livelihoods.